Comparison of the completeness of ICD-10 Coding of medicolegal deaths before and after the implementation of ‘History taking’ Proforma- A two year study (Journal of Forensic Medicine & Toxicology, 2025)
ICD – 10, also known as the International Statistical Classification of Diseases, is the international standard for defining  and reporting diseases, conditions and external causes that lead to the mortality or morbidity, thus aiding in comparison  and sharing of health information using a standardized, common language. ICD is used by physicians, nurses, research ers, health information managers and coders, health information technology workers, policy makers, insures and patient  organizations. Most countries use this system to report mortality data, which is a key indicator of health status. The pres ent study has been conducted as a one-year retrospective study and one year prospective study, giving emphasis on the  history taking part of medicolegal postmortem examinations conducted in GMCH, Chandigarh. The aim of the study  was to identify the defects in history taking by the use of Chapter XX of ICD-10, which focuses on the external causes of  mortality.
Keywords: ICD-10; History taking; External causes